The importance of monitoring in the Integrated Practice Teaching Service and Community in a Medical course in the North of the Brazil (Research, Society and Development, 2020)
This work aimed to report the experience of monitoring medical students as well as to evaluate the importance of the activities developed promoting the exchange of knowledge. Three students were selected to act as monitors of the PIESC axis from August 2019 to February 2020. The activities included the monitoring of academics in the first semester of the course as a way to facilitate their adaptation to the context of PIESC. In all activities we use the problematization methodology. From their reports at the end of the activities, we were able to evaluate their observations about the work they developed and how the experience enriched the students’ training. We can conclude that the experience was positive for the monitors. The activities allowed the interaction between teachers, students and health unit professionals as well as getting closer to the community. This experience greatly helps the construction of future professionals who act in a critical and humanistic way, since they build the ability to analyze the community in order to seek solutions to the most diverse problems. This conduct is important for the expansion of preventive medicine based on family and community.